Carbon dioxide reforming of methane over Ni catalysts prepared from Ni–Mg–Al layered double hydroxides: Influence of Ni loadings. (15th December 2015) - Lin, Xingyi; Li, Rule; Lu, Miaomiao; Chen, Chongqi; Li, Dalin; Zhan, Yingying; Jiang, Lilong
Highlights: CO disproportionation was significant at high Ni loadings. The catalyst stability at 1023 K tended to increase with increasing the Ni loading. The catalyst stability at 873 K decreased with increasing the Ni loading. Sintering of Ni particles was significant at high Ni loadings and at 873 K. Coke deposition was mainly responsible for the catalyst deactivation. Abstract: A series of supported Ni/Mg/Al catalysts with Ni loadings of 3–18 wt% were prepared from Ni–Mg–Al layered double hydroxides and tested for the CH4 –CO2 reforming. The influence of Ni loading on the catalyst activity and stability was studied. It is found that the catalyst activity increased with increasing the Ni loading. However, the CO disproportionation became significant as the Ni loading increased. The long-term stability of the Ni/Mg/Al catalysts was influenced by the Ni loading as well as the reaction temperature. At a high temperature of 1023 K, the catalyst stability increased with increasing the Ni loading, whereas it decreased with increasing the Ni loading at a low temperature of 873 K. The characterization on the spent Ni/Mg/Al catalysts showed that the sintering of Ni metal particles increased with increasing the Ni loading, and it became more severe at 873 K than at 1023 K. On the other hand, the coke deposition at 1023 K tended to decrease with increasing the Ni loading, and an opposite tendency was observed at 873 K. The coke deposition particularly the encapsulating carbon was considered to be responsible for the catalyst deactivation. A Ni loading of 12 wt% would be suitable for the Ni/Mg/Al catalyst considering its high activity, good stability, and less coke deposition at high temperature.